2020
DOI: 10.21203/rs.3.rs-51220/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aptamer targeted therapy potentiates immune checkpoint blockade in triple-negative breast cancer

Abstract: Background: Triple-negative breast cancer (TNBC) is a uniquely aggressive cancer with high rates of relapse due to resistance to chemotherapy. TNBC expresses higher levels of programmed cell death-ligand 1 (PD-L1) compared to other breast cancers, providing the rationale for the recently approved immunotherapy with anti-PD-L1 monoclonal antibodies (mAbs). A huge effort is dedicated to identify actionable biomarkers allowing for combination therapies with immune-checkpoint blockade. Platelet-derived growth fact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Cell and tumor lysates preparation and immunoblot analyses were performed as previously reported [34,35]. Filters were probed with the indicated primary antibodies: anti-EGFR, anti-phospho-44/42 MAPK (extracellular signal-regulated kinase 1/2, ERK1/2, indicated as pERK1/2), anti-caspase 3 and anti-vinculin (Cell Signaling Technology Inc., Danvers, MA), anti-ERK1 (C-16) (Santa Cruz Biotechnology, Santa Cruz, CA), antiphospho-histone H2A.X (Ser139, indicated as γH2AX), clone JBW301 (Upstate Biotechnology, Inc., Lake Placid, NY).…”
Section: Immunoblotmentioning
confidence: 99%
“…Cell and tumor lysates preparation and immunoblot analyses were performed as previously reported [34,35]. Filters were probed with the indicated primary antibodies: anti-EGFR, anti-phospho-44/42 MAPK (extracellular signal-regulated kinase 1/2, ERK1/2, indicated as pERK1/2), anti-caspase 3 and anti-vinculin (Cell Signaling Technology Inc., Danvers, MA), anti-ERK1 (C-16) (Santa Cruz Biotechnology, Santa Cruz, CA), antiphospho-histone H2A.X (Ser139, indicated as γH2AX), clone JBW301 (Upstate Biotechnology, Inc., Lake Placid, NY).…”
Section: Immunoblotmentioning
confidence: 99%
“…Currently, enormous effort is devoted to identifying novel actionable biomarkers that may allow combination therapies with immune checkpoint blockade in TNBC. Recently, our group demonstrated the efficacy of a novel combination treatment with the previously validated PDGFRβ aptamer [37,73,84] and anti-PD-L1 mAbs in both human and murine in vitro settings, consisting of TNBC cells cultured as monolayer or co-cultured with lymphocytes [92]. Importantly, the PDGFRβ aptamer (intravenous administration) potentiated the efficacy of the anti-PD-L1 antibody in inhibiting tumor growth and lung metastasis formation in a syngeneic 4T1 TNBC mouse model by acting on both tumor cells and immune populations.…”
Section: Aptamers For Complementing the Use Of Antibodiesmentioning
confidence: 99%
“…high rates of relapse due to resistance to chemotherapy, expresses higher levels of programmed cell death-ligand 1 (PD-L1) compared to other breast cancers, and thus provides the rationale for FDA-approved immunotherapy with anti-PD-L1 monoclonal antibodies (mAbs). Because platelet-derived growth factor receptor β (PDGFRβ) is overexpressed by TNBC cells and tumor microenvironment, Camorani et al 6 developed a PDGFRβ aptamer to investigate a novel combination treatment with the PDGFRβ aptamer and anti-PD-L1 mAbs in TNBC. Importantly, they found that the aptamer increases the antibody efficacy in inhibiting tumor growth and lung metastases in mice by acting on both tumor cells, inhibiting signaling pathways, and increasing intratumoral T cells.…”
Section: Breast Cancermentioning
confidence: 99%